2004
DOI: 10.1111/j.1469-8749.2004.tb01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Victimization: a newly recognized outcome of prematurity

Abstract: Victimization by peers affects 10 to 20% of school children under the age of 12 years. Physical, verbal, and psychological victimization (being pushed, hit, called names, teased, being the target of rumours, theft, extortion) is associated with short-and long-term adjustment problems, such as peer rejection, social withdrawal, low self-esteem, anxiety, loneliness, and depression, as well as academic problems and school drop-out. Research on populations of school children (primary and secondary) has associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…The current findings are consistent with previous studies investigating multiple predictors of behaviour (Girouard et al, 1998;Nadeau et al, 2001). The suggestion that cognitive attainment and learning difficulties pose risks for victimization (Nadeau et al, 2004) is furthermore consistent with our finding of an association between general cognitive function and specifically emotional behaviour problems. This interpretation of the findings suggests that within the preterm group, lower IQ scores are associated with more emotional problems, and worse prosocial behaviour skills.…”
Section: B Se B Betasupporting
confidence: 94%
“…The current findings are consistent with previous studies investigating multiple predictors of behaviour (Girouard et al, 1998;Nadeau et al, 2001). The suggestion that cognitive attainment and learning difficulties pose risks for victimization (Nadeau et al, 2004) is furthermore consistent with our finding of an association between general cognitive function and specifically emotional behaviour problems. This interpretation of the findings suggests that within the preterm group, lower IQ scores are associated with more emotional problems, and worse prosocial behaviour skills.…”
Section: B Se B Betasupporting
confidence: 94%
“…Further, a study of victimization by their peers of 96 children born extremely preterm, at age 7 years, was conducted by (Nadeau et al 2004). It was found that preterm children were more victimized by their peers than their full-term classmates, even when children with visible motor, cognitive, or sensory disabilities were excluded.…”
Section: Social/emotional/behavioral Adjustmentmentioning
confidence: 99%
“…10 Bullying occurs in forced group settings such as classrooms where children are grouped purely by age and many are strangers to each other initially. It is one strategy to obtain social dominance 22 that allows access to social or romantic relationships and material resources (e.g.…”
Section: Discussionmentioning
confidence: 99%